ECOLINGUISTICS-BASED PEDAGOGY FOR YOUNG LEARNERS: Eco-Teaching Practices in Nunleu, Kupang City-Indonesia - Tualaka, Dias P ora (Postgraduate School, Universitas Nusa Cendana, 2025)
This study explores the implementation of the eco-teaching approach in English language educationwithin the Kali Sembunyi learning community, located in Nunleu subdistrict, Kota Raja, Kupang City.The target group consists of children aged 6–10 years living near a local river basin. Eco-teachingintegrates ecolinguistic principles (Halliday & Mühlhäusler) and meaningful learning theory by utilizingenvironmental objects as direct teaching media. The learning process emphasizes interactive andjoyful activities grounded in the children’s ecological context.Using a descriptive qualitative method, data were collected through observation, interviews, anddocumentation. The results indicate that children acquired English vocabulary more effectively whenlearning was contextual and grounded in their surroundings, compared to traditional methodsinvolving translation and rote memorization. Engaging with real-world materials such as stones, leaves,and water fostered deeper cognitive and emotional involvement, making language acquisition moremeaningful. These findings support the view that language should be taught in connection withecological contexts to cultivate both linguistic competence and environmental awareness.This study recommends implementing eco-teaching across all age levels in foreign language education,particularly in community-based learning settings. Integrating language instruction with localecosystems not only enhances retention and understanding but also nurtures ecological sensitivityamong learners.